2023
DOI: 10.3390/cancers15020557
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Isolated Sesquiterpene Lactone and Hydroxyanthraquinone Induce Apoptosis in Oral Squamous Cell Carcinoma Cell Line

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most prevalent cancers worldwide, especially in Asian countries. The emergence of its drug resistance and its side effects demands alternatives, to improve prognosis. Since the majority of cancer drugs are derived from natural sources, it provides a window to look for more biocompatible alternatives. In this study, two natural compounds, costunolide (CE) and aloe emodin (AE), were isolated from the stem of Lycium shawii. The compounds were examined for their an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The scratch closures at IC 50 doses were smaller, measuring up to 17.2% at 24 hours and 35.8% at 48 h, reflecting the potential of the extract in reducing cell migration. Several in vitro studies have provided evidence that phytochemical compounds derived from L. shawii can impede the invasion and migration of various cell lines (Choi et al, 2013;Xiao and Guo, 2009;Shams et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The scratch closures at IC 50 doses were smaller, measuring up to 17.2% at 24 hours and 35.8% at 48 h, reflecting the potential of the extract in reducing cell migration. Several in vitro studies have provided evidence that phytochemical compounds derived from L. shawii can impede the invasion and migration of various cell lines (Choi et al, 2013;Xiao and Guo, 2009;Shams et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the successful preparation of stable nano-composites, we proceeded to study the inhibitory effects on HepG2 cells in vitro via an MTT test, morphological alterations, Annexin V-FITC/PI double staining method, cell cycle determination, ROS, and Δ Ψm level detection and obtained significant experimental results. As reported, the apoptotic cells were usually accompanied by some characteristic morphological features such as cellular membrane changes, shrinkage, nuclear concentration, and fragmentation [ 37 , 38 ]. The results demonstrated that AASP−SeNPs could effectively exert cytotoxicity and induce apoptosis in HepG2 cells, dose-dependently.…”
Section: Discussionmentioning
confidence: 98%
“…Costunolide isolated from the stem of Lycium shawii initiated apoptosis in oral squamous cell carcinoma (OSCC) cell line CAL 27. This compound upregulated Bak, amplified the levels of cleaved caspases 3 and 6, and anti-apoptotic factor BCL2L1 in this cell line ( Shams et al, 2023 ). In platinum-resistant human ovarian cancer cells (MPSC1 and SKOV3), costunolide has been shown to act stronger than cisplatin in decreasing cell viability.…”
Section: Sesquiterpene Lactones With Pro-apoptotic Activities In Cancermentioning
confidence: 91%